Tajweed learning through the support of Arabic phonetic - Harun Baharudin (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study shows the support and the role of phonetic Arabic in improving the methods of talaqqi musyafahah in learning tajweed of al-Quran. Tajweed has often been considered as a separate field of knowledge from the development of phonetics. Tajweed is seen as a science that adheres to the traditional method centred on memorization and imitation rather than by reference to scientific knowledge, which is the principle in Arabic phonetics. Both of these have the same goal, namely to maintain the reference in the context of the Arab pronunciation. The assumption that only talaqqi musyafahah is the best method in the learning of the al-Quran has become a factor as to why advancements in the field of phonetics are not fully applied to tajweed. Therefore, this study sought to 1) determine the differences between knowledge of Arabic phonetic in literature and some aspects of recitation and 2) find out similarities between several aspects found in the Arabic phonetics and tajweed which may help support the teaching and learning of tajweed of al-Quran. The methodology used in this study by comparing comparative analysis through existing literature, especially scholarly writing in phonetic and tajweed fields. This comparison analysis attempts to see the similarities and differences in the context of makhraj and the manner of articulation system (sifat hurf) in terms of definition of terms, methods and techniques of learning, and their measurements. The study found that there are some gaps between this knowledge in terms of understanding of the definition, sources and approaches in pedagogy. However, results show that the differences between these two fields of knowledge are intertwined and complement each other.